Application of the Qur’anic Pedagogical Style Through Repetition (Tikrar) to Improve Students’ Memory Retention and Its Relevance to Islamic Theology - Auni, Laila; Zuliana, Eka; Nasution, Nur Azizah (Edumaspul: Jurnal Pendidikan, 2026)
A major challenge for the education sector in the era of information disruption is the decline in students memory and the level of tauhid retention due to excessive exposure to social media. The pedagogical style of the Qur’an possesses distinctive characteristics in conveying its message. This study aims to explore the wealth of the Qur’an’s pedagogical style specifically the method of repetition (tikrar) and analyze its role in enhancing learners memory retention during the learning process. The research method employed is library research. Data were collected from various sources on exegesis, cognitive psychology, and learning theory. Research findings indicate that repetition in the Qur’an is not merely a reiteration of word, rather it serves as a strategy for conveying message or information from educator to learner facilitating the transfer from short term to long term memory with the aim that the message be implemented in daily life. The practical implications of this research can be realized through the design of a repetition based curriculum and interactive classroom teaching methods. In the context of theology, the repetition of the Qur’an fosters a steadfast conviction in learners regarding their lord, thereby shaping a minsed, attitude, and behavior consistent with Islamic teachings.